Performance evaluation of CORDEX South Asia models for projections of precipitation over the Kabul basin, Afghanistan. Issue 1 (31st December 2022) - Ghulami, Masoud; Gourbesville, Philippe; Audra, Philippe; Shie-Yui, Liong
ABSTRACT: Precipitation is one of the key input data for hydrological modelling and water resources assessment. Climate projections are regionally available at a finer resolution, but it is still necessary to validate such data against the observations before any application. In this study the precipitation data available from the Coordinated Regional Downscaling Experiment (CORDEX) program of the South Asian domain was examined against APHRODITE (Asian Precipitation – Highly-Resolved Observational Data Integration Towards Evaluation) precipitation, which is used as observations in the absence of in situ measurements for the data-scarce Kabul basin in Afghanistan. The evaluation methods include verification statistics as well as visual verification by mapping the data over the basin. The evaluation results showed that some of the RCMs (Regional Climate Models) are following an entirely different precipitation pattern both temporally and spatially; however, their driving GCMs might be the same. Six of the 17 RCMs examined in this study performed well for the Kabul basin. The ensemble results of these selected RCMs suggest a decreasing trend in the future precipitation under both RCPs (Representative Concentration Pathways), with variations ranging from −14% to +6% under RCP 4.5 and −17% to +8% under RCP 8.5 for most areas, especially in the central parts of the basin.